2019
DOI: 10.3390/md17050258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fucoidans from Five Different Brown Algae on Oxidative Stress and VEGF Interference in Ocular Cells

Abstract: Background: Fucoidans are interesting for potential usage in ophthalmology, and especially age-related macular degeneration. However, fucoidans from different species may vary in their effects. Here, we compare fucoidans from five algal species in terms of oxidative stress protection and vascular endothelial growth factor (VEGF) interference in ocular cells. Methods: Brown algae (Fucus vesiculosus, Fucus distichus subsp. evanescens, Fucus serratus, Laminaria digitata, Saccharina latissima) were harvested and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 50 publications
(72 reference statements)
4
71
3
Order By: Relevance
“…ARPE-19 cells as an RPE cell line are very resistant against hydrogen peroxide [26]. Therefore we used 0.5 mM tert-butyl hydroperoxide (TBHP) to lower the cell viability of ARPE-19 significantly after 24 h, as previously shown [19]. Again, the LD fucoidan showed no significant effect (Figure 4).…”
Section: Effects On Oxidative Stress Protectionmentioning
confidence: 79%
See 3 more Smart Citations
“…ARPE-19 cells as an RPE cell line are very resistant against hydrogen peroxide [26]. Therefore we used 0.5 mM tert-butyl hydroperoxide (TBHP) to lower the cell viability of ARPE-19 significantly after 24 h, as previously shown [19]. Again, the LD fucoidan showed no significant effect (Figure 4).…”
Section: Effects On Oxidative Stress Protectionmentioning
confidence: 79%
“…These optimizations of using SALy and alginate precipitation was used to prepare highly pure and fractionated fucoidans from S. latissima by ion-exchange chromatography (IEX), the purification method was described previously [15], while the bioactivity is tested here. SL was chosen, since previous work has shown that SL fucoidan has biological effects [19]. A further optimization was used, were the alginate was precipitated by CaCl 2 instead of acid, this method is believed to be gentler and is therefore likely to preserve the fucoidan structure better than the use of acid.…”
Section: Chemical Characterization Of the Fucoidansmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecklonia maxima is a brown seaweed typically found along the southern Atlantic coast of Africa. Polysaccharides from E. maxima have been reported to have anti-diabetes, anticancer, and antioxidant activities [22][23][24]. However, the cosmeceutical potential of polysaccharides isolated from E. maxima has not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%